A PROTOCOL FOR TESTING THE EFFICACY OF YOGA INTERVENTION IN MANAGING CHRONIC KIDNEY DISEASE OF UNKNOWN ETIOLOGY IN THE UDDANAM REGION - V Sasi Kala Boppadapu,; Dr. Ramesh M N,; Dr. Sri Krishna Chandaka,; Dr. Arun Thulasi, (The Bioscan, 2024)
Chronic Kidney Disease of Unknown Etiology (CKDu), a distinct form of CKD lacking traditional risk factors, has severely affected the Uddanam region of India, with a staggering 40-60% prevalence. Despite multiple investigations, the underlying causes remain elusive, highlighting the urgent need for complementary therapeutic approaches. Yoga, an ancient Indian practice with proven efficacy in various chronic illnesses, offers promising potential for CKDu management. This study aims to validate a yoga program for CKDu, assess its feasibility, and evaluate the efficacy of a three-month yoga intervention in alleviating symptoms and complications through comprehensive biochemical, physiological, and psychological assessments. Primary outcomes include biochemical markers, physiological parameters (e.g., blood pressure, body composition), and psychological assessments (quality of life, anxiety, stress). The validated and feasible yoga module is anticipated to demonstrate significant improvements in biochemical, physiological, and psychological outcomes in the intervention group compared to the control group. Positive results support the integration of yoga as an adjunctive therapy for CKDu management.